Leveraging Assessment Information for Enhancing Professional Learning in Educational Contexts - Basudev Gautam; Mani Ram Sharma (International Journal of Educational Review, 2023)
This article endeavors to provide a conceptual exploration of the multifaceted utilization of assessment information to enrich the sphere of professional learning. Employing a methodical review of secondary sources such as scholarly journal articles, authoritative reports, and pertinent online resources, the study adopts a foundation of content and thematic analysis. The findings of this study underscore the cyclical nature of assessment, encapsulated within the plan-do-check-act paradigm, and emphasize the paramount significance of assessment information for the continuous development of educators. Moreover, a central revelation of this inquiry pertains to the indispensable role of systematically collected assessment information in bolstering the quality of education through informed and tailored professional learning initiatives within educational institutions.